Efeito da somatotropina bovina recombinante no desempenho e nas características químicas da carne de bovinos - Chardulo, Luis Arthur Loyola [UNESP]; Silveira, Antonio Carlos [UNESP]; Furlan, Luiz Roberto [UNESP]; Arrigoni, Mario de Beni [UNESP]; Costa, Ciniro [UNESP]; De Oliveira, Henrique Nunes [UNESP] (My University, 1998)
The objective of this study was to evaluate the effects of the use of recombinant bovine somatotropin (rbST) in weight gain, feeding efficiency and chemical characteristics of meat of young bulls. Fifty nine young bulls were used: 30 crossbred Simmental x Nelore and 29 Nelore aging between seven to eight months, weighing 236 and 116 kg, respectively. A randomized experiment in a 2 × 2 factorial arrangement was used. There were two levels of rbST (0 and 250 mg/animal/14 days) and two breed groups subdivided in two experimental phases. Diet was based on corn silage and concentrate aiming at a weight gain of 0.8 a day for Phase I (70 days) and 1.3 kg for Phase II (98 days). Animals were slaughtered at 13 months of age and the measurements of carcass dressing and meat quality were taken. Results showed that cross-breeding animals overcame (p<.01) the Nelore breed in weight gain and final weight at slaughtering. Use of rbST has not influenced weight gain, final weight, carcass weight and chemical characteristics of meat (p>.05). The use of rbST improved feeding efficiency 11.91 % for cross-bred and 24.32% for Nelore in Phase II.

O presente estudo objetivou avaliar as respostas da aplicação da somatotropina bovina recombinante (rbST) no ganho de peso, eficiência alimentar e características químicas da carne de bovinos jovens. Foram utilizados 59 bovinos inteiros: 30 mestiços Simmental x Nelore e 29 Nelores com idade entre sete a oito meses e pesos de 236 e 116 kg, respectivamente. O delineamento experimental foi o inteiramente casualizado em esquema fatorial 2 x 2, com dois níveis de rbST (0 e 250 mg/animal/14 dias) e dois grupos raciais, subdivididos em duas fases experimentais. A dieta consistiu de silagem de milho e concentrado, balanceada para ganho diário de 0,8 kg na Fase I (70 dias) e 1,3 kg na Fase II (98 dias). Os animais foram abatidos aos 13 meses de idade e analisados quanto ao rendimento de carcaça e características químicas do músculo Longissimus dorsi. Os resultados mostraram que os animais mestiços superaram (P < 0,01) os da raça Nelore quanto ao ganho de peso e peso final de abate. A suplementação com rbST, independentemente da raça, não influenciou o ganho de peso, peso final, peso de carcaça e as características químicas da carne (P > 0,05). A aplicação da rbST melhorou a eficiência alimentar em 11,91% nos mestiços e em 24,32% nos Nelore, na Fase II do experimento.
Effects of recombinant bovine somatotropin on performance and chemical characteristics of meat of bulls
Keywords: Bovine growth; Growth hormone; Meat quality; Precocity